Roles of Career Maturity Mediating the Effects of Internal Locus of Control and Socioeconomic Status on Career Readiness of Vocational High School Students - Paraswati, Khoiru Indah; Marsofiyati, Marsofiyati; Suherdi, Suherdi (Transpublika Publisher, 2025)
The goals of this study are to demonstrate and examine how socioeconomic status and internal locus of control affect Career Readiness through the mediation of career maturity. This study uses primary data and quantitative methods. Students in the XII grade at SMK Negeri 45 West Jakarta made up the study's population, and 163 research samples were collected using the Slovin formula. Proportionate stratified random sampling was the method used for the sampling. Path analysis using SmartPLS version 4.1.0.9 was the data analysis technique employed in this study. This study makes reference to Hair et al. The findings showed that internal locus of control has a positive and significant effects on career maturity and career readiness, socioeconomic status has a negative effect on career maturity and career readiness, career maturity has a positive and significant effects on career readiness, career maturity is able to mediate the effect of internal locus of control on work readiness, but career maturity is not capable to mediate the effect of socioeconomic status on work readiness.